2006
DOI: 10.1007/s00540-006-0439-0
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged loss of leg myogenic motor evoked potentials during thoracoabdominal aortic aneurysm repair, without postoperative paraplegia

Abstract: No postoperative paraplegia occurred in a patient whose leg myogenic motor evoked potentials (mMEPs) disappeared during thoracoabdominal aortic aneurysm repair. A 69-year-old man underwent resection and repair of a type III (Crawford classification) thoracoabdominal aneurysm. An epidural catheter was placed into the epidural space for epidural cooling, and a Swan-Ganz catheter was placed into the subarachnoid space for cerebrospinal fluid (CSF) drainage. Continuous CSF pressure and temperature measurement was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…They retrospectively reviewed SSEP and MEP monitoring in 60 patients who underwent thoracoabdominal repairs, with a paraplegia rate of 10.5%. Denda et al reported a similar case study in which a TAAA surgery patient had persistent loss of MEPs with no subsequent paraplegia, resulting in a false positive. Both studies utilized epidural cooling as a protective adjunct against spinal cord ischemia.…”
Section: Discussionmentioning
confidence: 98%
“…They retrospectively reviewed SSEP and MEP monitoring in 60 patients who underwent thoracoabdominal repairs, with a paraplegia rate of 10.5%. Denda et al reported a similar case study in which a TAAA surgery patient had persistent loss of MEPs with no subsequent paraplegia, resulting in a false positive. Both studies utilized epidural cooling as a protective adjunct against spinal cord ischemia.…”
Section: Discussionmentioning
confidence: 98%
“…MEPs are elicited through transcortical electrical stimulation and may provide increased sensitivity and specificity for identification of spinal cord ischemia when compared to SSEPS (Jacobs et al 2006;Denda et al 2006;Kakinohana et al 2007;Kawanishi et al 2007;Shine et al 2008). Myogenic potentials are recorded from muscles in the extremities by delivering multipulse, electrical stimulation to the scalp overlying the motor cortex.…”
Section: Other Methods Of Ischemia Detectionmentioning
confidence: 99%